2018
DOI: 10.1051/matecconf/201821703002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Hissing-Type Noise and Vibration of the Automotive HVAC System

Abstract: Noises such as hissing, humming, air-rush and compressor engagement are the common type of noises that can be induced from the automotive heating and ventilating air conditional (HVAC) system. These noises are basically generated from the effects of vibrational HVAC components. Due to this, the root cause of the noises has to be investigated for any implementation of solution. In this study, the hissing-type of noise is taken into consideration whereby the noise and vibration are measured from various HVAC com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…It is produced when the liquid refrigerant is forced to flow through a small size orifice (Thawani et al, 2013). Paiman et al (2018) found that the evaporator component has contributed to this noise at the operating frequency of 4500-5000 Hz. Contrastingly, Thawani et al (2005) found that the thermal expansion valve (TVX) was a major contributor to the hissing noise.…”
Section: Introductionmentioning
confidence: 99%
“…It is produced when the liquid refrigerant is forced to flow through a small size orifice (Thawani et al, 2013). Paiman et al (2018) found that the evaporator component has contributed to this noise at the operating frequency of 4500-5000 Hz. Contrastingly, Thawani et al (2005) found that the thermal expansion valve (TVX) was a major contributor to the hissing noise.…”
Section: Introductionmentioning
confidence: 99%